MINAT SISWA PUTRA KELAS XI TAHUN AJARAN 2019/2020 TERHADAP E-SPORT (ELECTRONIC SPORT / OLAHRAGA ELEKTRONIK) DIVISI MOBILE LEGENDS BANG-BANG DI SMA NEGERI 11 SEMARANG (Universitas Negeri Semarang, 2020)
ABSTRACT Idhohuddin. 2020. The Interest of XI Grade Students In The Academic Year Of 2019/2020 Towards E-Sport Mobile Legends Bang – Bang Division At Senior High School State 11 Semarang. Final Project. Department of Elementary School Teacher Education of Physical Education. Faculty of Sport Science. Universitas Negeri Semarang. Advisor: Dr. Agung Wahyudi, S.Pd., M.Pd. Key Words: E-Sport, Mobile Legends, Interest, Student This research is motivated by the development of technology, which emerged new branches of sport that utilize the latest models that are electronic media namely E-Sport. Moreover, many of the students of Senior High School State 11 Semarang play video games. E-Sport is a competitive video games. E-Sport is one of the sport branches in Asia Games Exhibition 2018 and also in SEA Games 2019. The problem in this study is how the interest of male students in grade XI towards the E-Sport Mobile Legends Bang-Bang at Senior High School State 11 Semarang. The purpose of this study is to determine how the interest of male students in grade XI towards the E-Sport Mobile Legends Bang-Bang at Senior High School State 11 Semarang. The quantitative descriptive study uses a survey method. The variable of this study is the interest of male students of Senior High School State 11 Semarang also as population. The sample is 70 male students using a proportionate stratified random sampling technique. The data collection procedure using observation, documentation, and questionnaire. The instrument is a questionnaire. Descriptive percentage of statistical data analysis as a data analysis technique. The result of this study indicates that male students of grade XI academic year 2019/2020 towards E-Sport Mobile Legends Bang-Bang Division at Senior High School State 11 Semarang had an average interest in the E-Sport Mobile Legends Bang – Bang Division by 75.54%. Its shown that the interest of male students of grade XI at Senior High School State 11 Semarang categorized as high. Male students of grade XI of the Social Science Department have an average interest in E-Sport Mobile Legends Bang – Bang Division by 77.41% which is categorized as high. While for male students of grade XI of the Mathematics and Natural Science Department have an average interest in E-Sport Mobile Legends Bang – Bang Division by 73,06% which is also categorized as high. Based on the result of the study, it can be concluded that the interest of male students of grade XI in the academic year 2019/2020 at Senior High School 11 Semarang categorized as high. The researcher suggests to those who have an interest towards E-Sport is guided and directed to be professional. The school is also expected to be able to accommodate their interest in E-Sport by facilitating them.